Answer:
[tex]E(X^2)=32.5\\V(X)=7.5\\E[X(X-1)]=E(X^2)-E(X)\\V(X)=E(X^2)-[E(X)]^2[/tex]
Step-by-step explanation:
We have the following properties:
[tex]E( X + Y ) = E(X) + E(Y)\\V(X) = E(X^2)-[E(X)]^2[/tex]
So, if we have that E[X(X-1)] = 27.5, we can write them using the first property as:
[tex]E(X(X-1))=27.5\\E(X^2-X)=27.5\\E(X^2)-E(X)=27.5[/tex]
Then, replacing E(X) by 5 and solving for [tex]E(X^2)[/tex], we get:
[tex]E(X^2)-5=27.5\\E(X^2)=27.5+5\\E(X^2)=32.5[/tex]
Finally, using the second property and replacing [tex]E(X)[/tex] by 5 and [tex]E(X^2)[/tex] by 32.5, we get that V(X) is equal to:
[tex]V(X) = 32.5 - 5^2\\V(X) =32.5 - 25\\V(X) = 7.5[/tex]